2017
DOI: 10.18203/2320-1770.ijrcog20172932
|View full text |Cite
|
Sign up to set email alerts
|

Study of adaptability and efficacy of menstrual cup in managing menstrual health and hygiene

Abstract: Background: Menstrual cups have been available for decades, but their use is limited by bulky design and the need for multiple sizes. However, some benefits have been reported like improvement in managing health and hygiene during menstruation, better information on the average menstrual fluid discharged by women during menstruation and attainment of more knowledge bridging the lacuna in knowledge about the adaptability and efficacy of menstrual cup as a better alternative to conventional options. The study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 6 publications
4
47
0
5
Order By: Relevance
“…In one case report, severe pain on removal was self-reported and in another case report severe pain was self-reported when wearing the menstrual cup, 14 and two participants in two different cohort studies reported vaginal or cervical irritation without clinical consequences 39, 41. Three adverse events that were reported in one cohort study and three case reports were possibly related to an allergy; one case of silicone allergy necessitated reconstructive vaginal surgery 13, 14, 48. Difficulty with removal that required professional assistance—an adverse event we did not anticipate—was reported 47 times for cervical cups (one participant from a cohort study, and 46 case reports) and twice for vaginal cups (both case reports) 13, 14, 46, 63…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In one case report, severe pain on removal was self-reported and in another case report severe pain was self-reported when wearing the menstrual cup, 14 and two participants in two different cohort studies reported vaginal or cervical irritation without clinical consequences 39, 41. Three adverse events that were reported in one cohort study and three case reports were possibly related to an allergy; one case of silicone allergy necessitated reconstructive vaginal surgery 13, 14, 48. Difficulty with removal that required professional assistance—an adverse event we did not anticipate—was reported 47 times for cervical cups (one participant from a cohort study, and 46 case reports) and twice for vaginal cups (both case reports) 13, 14, 46, 63…”
Section: Resultsmentioning
confidence: 97%
“…Of 436 unique records identified (appendix p 6), 59 were identified as relevant (figure 1), and 43 studies were included in our analysis (table 1). In these 43 studies, 3319 participants used or were asked about the menstrual cup 5, 13, 14, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73. Seven studies were completed among schoolgirls (ie, aged 12–19 years) in low-income and middle-income countries (647 [19·5%] participants) 5, 27, 33, 43, 58, 59.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the researchers called for deeper research and exploration to understand acceptability across different contexts, especially given that taboos related to vaginal insertion and an uninformed linkage with virginity in several low and middle-income countries, persist. 24 It is also timely that a recent 2019 systematic review indicates that menstrual cups are a safe option for menstruation management and are being used internationally. 25 In previous studies showed that the use of a menstrual cup there was no mechanical harm in the vagina and cervix during follow up when examined.…”
Section: Discussionmentioning
confidence: 99%